1988
DOI: 10.1126/science.2969619
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic CD4 Peptide Derivatives That Inhibit HIV Infection and Cytopathicity

Abstract: Synthetic peptide segments of the CD4 molecule were tested for their ability to inhibit infection of CD4+ cells by the human immunodeficiency virus (HIV) and to inhibit HIV-induced cell fusion. A peptide mixture composed of CD4(76-94), and synthesis side products, blocked HIV-induced cell fusion at a nominal concentration of 125 micromolar. Upon high-performance liquid chromatography, the antisyncytial activity of the peptide mixture was found not in the fraction containing the peptide CD4(76-94) itself, but i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

1989
1989
2010
2010

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(77 citation statements)
references
References 35 publications
2
75
0
Order By: Relevance
“…Investigations on the regions of CD4 other than the gp 120 binding site involved in HIV-1 envelope-mediated membrane fusion have provided contradictory data (Lifson et al, 1988;Camerini & Seed, 1990;Ohki et al, 1990;Rausch et al, 1992;Broder & Berger, 1993). The role of the anti-CDR3 MAb 13B8-2, specific for sequences surrounding amino acid 87, is also controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations on the regions of CD4 other than the gp 120 binding site involved in HIV-1 envelope-mediated membrane fusion have provided contradictory data (Lifson et al, 1988;Camerini & Seed, 1990;Ohki et al, 1990;Rausch et al, 1992;Broder & Berger, 1993). The role of the anti-CDR3 MAb 13B8-2, specific for sequences surrounding amino acid 87, is also controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Potent non-peptide inhibitors of L-type calcium-dependent voltage channels have been identified as low-molecular weight contaminants extractable from plasticware frequently used in peptide purification [141]. Thus, even in purified or synthetic preparations of peptides, no biological activity can reasonably be attributed to the peptide present in the mixture unless biological activity is preserved upon acid treatment or boiling, preserved upon treatment with presumptive processing enzymes, and most importantly, abolished by Pronase treatment (e.g., [142]). …”
Section: Abolition Of Activity By Maneuvers That Destroy Peptides or mentioning
confidence: 99%
“…Chromostatin is a fragment of chromogranin A (CGA- (124)(125)(126)(127)(128)(129)(130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142)(143) in the cow) which represents a special case of potential extracellular processing of CGA. Simon and co-workers described an inhibitory effect of purified chromogranin A on catecholamine release from the adrenal medulla.…”
mentioning
confidence: 99%
“…Preliminary data from our group (12) suggested that they could act, at least in part, by occluding a region of CD4 (i.e., CDR3) which may be important for the fusion process (21,22,37). These results are supported by biochemical studies previously reported by Autiero et al (1).…”
Section: Inhibition Of Hiv-1 and Hiv-2 Infection Ofmentioning
confidence: 99%